Perceptions of Parents on Management of Food Allergy in Children with Autism Spectrum Disorder (ASD) in Saudi Arabia - Talal E. Alhuzimi; Mudi H. Alharbi (MDPI AG, 2022)
Background: Food allergy is one of the most serious health concerns spread across the globe. Its awareness and management are undervalued, especially in children with autism spectrum disorders (ASD). The aim of this study is to explore the perception of parents of autistic children from Saudi Arabia on the prevalence, knowledge, awareness and management of food allergens. Methods: A cross-sectional exploratory self-administrated online survey was conducted in Saudi Arabia, where 125 parents of autistic children voluntarily took part in the survey from April to August 2022. Results: This study indicates that less than one-fourth of autistic children suffering from food allergies, while most of them are allergic to proteins mainly. Examination of the knowledge level of these parents regarding food allergies, depending upon the score of correct answers given by them, showed that a majority of parents had a moderate level of knowledge on food allergy. Even though there was awareness about food allergens, the use of medical interventions was not employed much. However, the parents were mindful of food labeling and found it to be useful in avoiding known food allergies. Mediating effects of food allergy were observed in the relationship between food allergy knowledge and its management. Moreover, the source of information about food allergies was also found to be significantly associated with the knowledge score and the level of awareness regarding food allergies. This study provides evidence that there is a significant influence of food allergy knowledge of parents of autistic children on its management among autistic children from Saudi Arabia, with awareness of food allergies as the mediator. Conclusions: This is the first study where the prevalence, knowledge and management, along with awareness of food allergy, has been empirically explored through the perception of parents of autistic children.